2017
DOI: 10.1007/s10549-017-4565-1
|View full text |Cite|
|
Sign up to set email alerts
|

Measuring and understanding adherence in a home-based exercise intervention during chemotherapy for early breast cancer

Abstract: Inexpensive commercial-grade activity trackers, with data uploaded directly into research computers, enable objective monitoring of home-based exercise interventions in adults diagnosed with cancer. Analysis of the association of walking steps with participant characteristics at baseline and toxicities during chemotherapy can identify reasons for low/non-adherence with prescribed exercise regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 58 publications
4
42
2
Order By: Relevance
“…Our analyses should be interpreted as exploratory, since the study was not primarily powered for the current study; consequently, additional predictors might have been missed. In other studies, exercise facility location [20], fewer endocrine symptoms [13], lower durations of exercise [13], fewer exercise limitations [13], shorter chemotherapy protocol [13], exercise history [19], being employed[18, 21], high income [21], early stage disease [18] and being Caucasian [22] were found as predictors for adherence, while these predictors were not assessed in this study. In univariate analyses, several predictors were found to be significant but were not supported in the multivariable analysis, which might have been the result of multicollinearity or restricted statistical power.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Our analyses should be interpreted as exploratory, since the study was not primarily powered for the current study; consequently, additional predictors might have been missed. In other studies, exercise facility location [20], fewer endocrine symptoms [13], lower durations of exercise [13], fewer exercise limitations [13], shorter chemotherapy protocol [13], exercise history [19], being employed[18, 21], high income [21], early stage disease [18] and being Caucasian [22] were found as predictors for adherence, while these predictors were not assessed in this study. In univariate analyses, several predictors were found to be significant but were not supported in the multivariable analysis, which might have been the result of multicollinearity or restricted statistical power.…”
Section: Discussionmentioning
confidence: 77%
“…Patients who perceived a higher importance of exercise, who had an early stage of disease, and who were employed had a higher compliance with exercise intensity [18]. The study of Nyrop et al reported that being Caucasian or reporting higher walking minutes prior to the start of chemotherapy was associated with greater walking steps per week in a home-based exercise intervention [22]. To our knowledge, no studies were performed reporting predictors about compliance in supervised exercise programs during treatment in breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…There are a few examples in which the use of technology can support virtual cancer exercise and cancer rehabilitation systems, but they need further testing for feasibility, usability, acceptability, and implementation for a variety of populations. 46,47 Telehealth care is one type of delivery that needs further testing but recently was found to improve function, decrease pain, and decrease health care service use, 37 aiding community clinicians and increasing the reach of cancer rehabilitation in rural and/or low-resource settings. 48 The use of technology also can revolutionize the evaluation of value metric reporting, and by adding real-time assessment of outcomes and quality.…”
Section: ) Improve Evidence Regarding Drivers Of Variations In Care mentioning
confidence: 99%
“…Symptom experience may have been moderated in women who engaged in walking during chemotherapy compared with those who did not engage in walking. We previously reported that engaging in moderate walking during chemotherapy is very challenging, even among women aged <65 years who were enrolled in our intervention studies 29 …”
Section: Discussionmentioning
confidence: 99%